Genomic Insights Into Energy Metabolism of Carboxydocella thermautotrophica Coupling Hydrogenogenic CO Oxidation With the Reduction of Fe(III) Minerals - Toshchakov, Stepan V.; Lebedinsky, Alexander V.; Sokolova, Tatyana G.; Zavarzina, Daria G.; Korzhenkov, Alexei A.; Teplyuk, Alina V.; Chistyakova, Natalia I.; Rusakov, Vyacheslav S.; Bonch-Osmolovskaya, Elizaveta A.; Kublanov, Ilya V.; Gavrilov, Sergey N. (Frontiers in Microbiology, 2018)
The genus Carboxydocella forms a deeply branching family in the class Clostridia and is currently represented by three physiologically diverse species of thermophilic prokaryotes. The type strain of the type species, Carboxydocella thermautotrophica 41T, is an obligate chemolithoautotroph growing exclusively by hydrogenogenic CO oxidation. Another strain, isolated from a hot spring at Uzon caldera, Kamchatka in the course of this work, is capable of coupling carboxydotrophy and dissimilatory reduction of Fe(III) from oxic and phyllosilicate minerals. The processes of carboxydotrophy and Fe(III) reduction appeared to be interdependent in this strain. The genomes of both isolates were sequenced, assembled into single chromosome sequences (for strain 41T a plasmid sequence was also assembled) and analyzed. Genome analysis revealed that each of the two strains possessed six genes encoding diverse [Ni,Fe]-CO-dehydrogenases (maximum reported in complete prokaryotic genomes), indicating crucial role of carbon monoxide in C. thermautotrophica metabolism. Both strains possessed a set of 30 multiheme c-type cytochromes, but only the newly isolated Fe-reducing strain 019 had one extra gene of a 17-heme cytochrome, which is proposed to represent a novel determinant of dissimilatory iron reduction in prokaryotes. Mössbauer studies revealed that strain 019 induced reductive transformation of the abundant ferric/ferrous-mica mineral glauconite to siderite during carboxydotrophic growth. Reconstruction of the C. thermautotrophica strains energy metabolism is the first comprehensive genome analysis of a representative of the deep phylogenetic branch Clostridia Incertae Sedis, family V. Our data provide insights into energy metabolism of C. thermautotrophica with an emphasis on its ecological implications.